Housing microfinance and housing financialisation in a global perspective. Issue 4 (2nd October 2021) - Grubbauer, Monika; Mader, Philip
Abstract: The application of microfinance to the provision, improvement or adaptation of housing—'housing microfinance'—is an increasingly significant area of practice and research interest. Housing microfinance has proliferated, predominantly but not exclusively in the global South. Its proliferation must be understood in the context of financialisation and the concurrently growing importance of financial self-help and private real estate investment. Promoter perspectives emphasise the affordability of microfinance solutions for housing, their appropriateness for incremental housing strategies, and potentially interesting new business models. Critical perspectives emphasise the high costs and continual need for subsidies, risks faced by borrowers and the discipline demanded from them. To advance the debate, we present an analytical typology which maps different housing microfinance approaches in terms of how they connect finance with housing, whether they are credit-led or savings-led, whether the market or the state dominates, whether they are individualistic or community-oriented, and how formal or informal they are. The five articles in this special issue, presenting material from Kenya, Mexico, U.S.A, Thailand and Argentina, collectively advance six avenues of research on housing microfinance: (1) its immediate social impacts; (2) wider impacts in terms of housing affordability, markets and policies; (3) implications for construction and retailing markets; (4) consequences for urban development and societies, (5) the financial work required from participants; (6) and the significance of the ongoing experimentation in housing microfinance.